Respuesta :

Answer:

Step-by-step explanation:

5x+20 = 0

5X= -20

X= -20/5 = -4

8(4n+3) = 32n+24 =0

32n = -24

n = -24/32 = -3/4

12n-6=0

12n =6

n = 6/12 = 1/2

9(2x+9)

18x+81 =0

18x= -81

x= -81/18 = -9/2= -4.5

36+9y=0

36=-9y

36/-9 = y = -4

7(n-3) = 0

7n-21=0

7n = 21

n = 21/7

n=3

21+15a = 0

21= -15a

a= 21/-15 = 7/-5 = -1.4

32x-12x=0

20x=0

x=0/20 = 0

n-4-9=0

n-13=0

n=13

-3x-9+15x=0

-3x+15x-9 =0

12x-9=0

12x=9

x=9/12 = 3/4 = 0.75

-16N-14N=0

-30n=0

n=0/-30 =0

-10-90x-6x-10x²-2

-10-2-96x-10x²

-12-96x-10x²

10x²+96x+12

x= -b±√b²-4(a)(c)/2a

   {-96±√96²-4(10)(12)}/2(10)

{-96±√(9216-480)}/20

-96±√8736/20

-96±(93.4665715644)/20

-96+93.4665715644/20        -96-93.4665715644/20

-2.5334284356/20                 -189.466571564/20

-0.12667142178≅ -0.13             -9.4733285782≅ -9.47

-0.13                                                -9.47

-5(9n+9) =0

-45n-45 =0

-45n = 45

n = 45/-45 =-1

-5n+3(6+7n)

-5n+18+21n=0

-5n+21n+18 =0

16n+18 =0

16n = -18

n = -18/16 = -9/8 = -1.125

-4+7(1-3n)=0

-4+7-21n=0

3-21n=0

3=21n

3/21=n = 1/7

3n-(2n-8)

3n-2n+8=0

n+8=0

n=-8